2015
DOI: 10.1186/s13578-015-0055-5
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 inhibits adipogenesis and promotes myogenic differentiation in C3H10T1/2 pluripotent cells by regulating Wnt signaling

Abstract: BackgroundThe directed differentiation of mesenchymal stem cells (MSCs) is tightly controlled by a complex network. Wnt signaling pathways have an important function in controlling the fate of MSCs. However, the mechanism through which Wnt/β-catenin signaling is regulated in differentiation of MSCs remains unknown. SIRT1 plays an important role in the regulation of MSCs differentiation.ResultsThis study aimed to determine the effect of sirtuin 1 (SIRT1) on adipogenesis and myogenic differentiation of C3H10T1/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 34 publications
0
41
1
Order By: Relevance
“…28 Conversely, Chen et al 50 indicated that miR-181a sensitized human malignant glioma cells to radiation; however, the role of miR-181a in human glioma chemoresistance, and more importantly, the downstream target and regulation mechanism that miR-181a regulated human glioma tumorigenesis, still needed more exploration. 33,34 Our sample analysis identified that the expression of miR-181a was lower in tumors than nontumor tissues. 30,35,37,42 These effects have been linked to cell behaviors, involving cell growth, differentiation, migration, and survival.…”
Section: Discussionmentioning
confidence: 96%
“…28 Conversely, Chen et al 50 indicated that miR-181a sensitized human malignant glioma cells to radiation; however, the role of miR-181a in human glioma chemoresistance, and more importantly, the downstream target and regulation mechanism that miR-181a regulated human glioma tumorigenesis, still needed more exploration. 33,34 Our sample analysis identified that the expression of miR-181a was lower in tumors than nontumor tissues. 30,35,37,42 These effects have been linked to cell behaviors, involving cell growth, differentiation, migration, and survival.…”
Section: Discussionmentioning
confidence: 96%
“…SIRT1 is knocked down by antisense oligonucleotides; consequently, the SIRT1 expression in MSCs is downregulated, and this finding demonstrates that SIRT1 can functionally inhibit osteogenesis and induce adipogenesis [24]. Our previous study found that resveratrol blocks adipocyte formation and promotes myotube differentiation in the established MSC commitment and differentiation model based on 5-azacytidine, which is a DNA methylation inhibitor [15]. By contrast, nicotinamide enhances the adipogenic potential of C3H10T1/2 cells [15].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study found that resveratrol blocks adipocyte formation and promotes myotube differentiation in the established MSC commitment and differentiation model based on 5-azacytidine, which is a DNA methylation inhibitor [15]. By contrast, nicotinamide enhances the adipogenic potential of C3H10T1/2 cells [15]. These studies implied that SIRT1-induced adipogenic suppression occurs throughout the whole process, particularly in the terminal differentiation of adipocyte and commitment differentiation of MSCs to a pre-adipocyte fate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations